Constitutional legality regarding the rights and legal duties to receive a COVID-19 vaccine: Case study from the Federal Republic of Germany - Bauer , Sunisa (CMU Journal of Law and Social Sciences, 2021)
Due to the current situation of the COVID-19 pandemic, a vaccine is the hope for the world to cease the spread of this pandemic. However, to apply the vaccinations to the people may lead to a legal argument. As in the Federal Republic of Germany, for instance, the constitutional validity of the law should a state provide its citizens the duty to receive the vaccine. Although a German pharmaceutical company, is a joint investor to produce the COVID-19 vaccine and the Government of Germany will provide the vaccines for its people without payment. The Constitutional Court of the Federal Republic once ruled that the procedures under the German Infection Protection Act (Infektionsschutzgesetz) and the Measles Protection Act (Masernschutzgesetz) for children entering state pre-kindergarden schools shall receive the Measles vaccine beforehand, is a legitimate procedure under the Federal Republic’s Constitution. Until now, the Government of the Federal Republic chooses to allow such decision to be decided and determined by the people to whether or not such person would receive a COVID-19 vaccine. Furthermore, the Government of Germany must deal with the argument of the constitutional validity of the rights to receive a COVID vaccine (Coronavirus-Impfverordnung – CoronaImpfV) which classifies people in age, health and occupation etc. and the rights to receive the vaccine as the first groups. Such measures are being argued relating to the principle of equality by the constitution. This study aims to provide the principle of the legality of the constitution for the measures of the law to specify the rights and duties to receive the COVID-19 vaccines by exampling the Federal Republic of Germany as a case study. Which can be analyzed and compared for the situation in Thailand should the legal measures be provided for the people to receive the COVID-19 vaccines in the future.